2021
DOI: 10.1016/j.envint.2021.106747
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to endocrine disrupting chemicals (EDCs) and cardiometabolic indices during pregnancy: The HOME Study

Abstract: Background: Toxicology studies have identified pregnancy as a window of susceptibility for endocrine disrupting chemicals (EDCs) and cardiometabolic indices in women. No study in humans, however, has examined EDC mixtures and cardiometabolic indices during pregnancy. Methods: We used the Health Outcomes and Measures of the Environment (HOME) Study to examine whether bisphenol A (BPA), polybrominated diphenyl ethers (PBDEs), per- and polyfluoroalkyl substances (PFAS), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 84 publications
2
16
0
Order By: Relevance
“…To the best of our acknowledge, only one epidemiologic study has assessed the relationship between urinary phthalate metabolites and circulating lipid biomarker levels during pregnancy [37]. In a cross-sectional analysis in which both urine and blood samples were collected at approximately 16 weeks of gestation, Vuong et al reported that urinary MBzP was negatively associated with total cholesterol levels, and it was also an important contributor in the mixture models examining circulating triglycerides among 388 pregnant women participating in the Health Outcomes and Measures of the Environment (HOME) Study [37]. In a different study on pregnancy exposures in relation to post-natal lipids, Wu et al prospectively investigated pregnancy urinary phthalate metabolite concentrations in relation to 4-8 years post-delivery lipid biomarker levels in 618 Mexican women [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our acknowledge, only one epidemiologic study has assessed the relationship between urinary phthalate metabolites and circulating lipid biomarker levels during pregnancy [37]. In a cross-sectional analysis in which both urine and blood samples were collected at approximately 16 weeks of gestation, Vuong et al reported that urinary MBzP was negatively associated with total cholesterol levels, and it was also an important contributor in the mixture models examining circulating triglycerides among 388 pregnant women participating in the Health Outcomes and Measures of the Environment (HOME) Study [37]. In a different study on pregnancy exposures in relation to post-natal lipids, Wu et al prospectively investigated pregnancy urinary phthalate metabolite concentrations in relation to 4-8 years post-delivery lipid biomarker levels in 618 Mexican women [51].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women represent a vulnerable study population to endocrine-disrupting chemical exposure, including phthalates, with potential consequences not only for maternal health but also to offspring health [36]. Yet, to the best of our knowledge, only one study has examined the association between urinary concentrations of phthalate metabolites and circulating lipid biomarker levels in pregnant women from the general population [37]. This study showed that concentrations of some phthalate metabolites were positively associated with circulating tryglicerides and total cholesterol during pregnancy.…”
Section: Introductionmentioning
confidence: 87%
“…All analysed subjects had detectable BDE-47 levels and 279 subjects were tested for the remaining PBDEs. As also discussed above, Vuong et al (2021) focused on blood pressure, glucose, and lipids in the pregnant women. Mean maternal serum concentrations of BDE-28 and -47 were 1.1 and 20.7 ng/g lipid, respectively.…”
Section: Cardiovascularmentioning
confidence: 99%
“…All analysed subjects had detectable BDE-47 levels and 279 subjects were tested for the remaining PBDEs. Vuong et al (2021) focused on blood pressure, glucose, and lipids in the pregnant women. Non-fasting glucose levels were measured at 1-h after drinking 50 g glucose load (n = 234), with the average assessment completed at ~ 27.6 ± 1.4 weeks gestation.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation